2020
DOI: 10.3390/vaccines8040584
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Adapted Live Attenuated SARS-Cov-2 Vaccine Completely Protects Human ACE2 Transgenic Mice from SARS-Cov-2 Infection

Abstract: A safe and effective vaccine that can provide herd immunity against severe acute respiratory syndrome coronavirus (SARS-CoV-2) is urgently needed to stop the spread of this virus among humans. Many human viral vaccines are live, attenuated forms of viruses that elicit humoral and cellular immunity. Here, we describe a cold-adapted live-attenuated vaccine (SARS-CoV-2/human/Korea/CNUHV03-CA22 °C/2020) developed by gradually adapting the growth of SARS-CoV-2 from 37 °C to 22 °C in Vero cells. This vaccine can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 52 publications
3
36
0
4
Order By: Relevance
“…By 6 dpc, mice in G3 (high virus dose/vehicle, white symbols) showed about 20% weight loss and by 8 dpc there were no survivors because they have either succumbed to the infection or had to be humanely euthanized due to severe clinical signs (lethargy, ruffled fur, labored breathing, and/or ≥25% body weight loss, Fig 2D). These observations are consistent with previous reports 20,21,24,25 . G4 mice (high virus dose/GC-376) showed similar clinical signs but such progression was delayed by about 24 h (~15% weight loss by 6 dpc).…”
Section: Modest Effect Of Gc-376 Treatment On the Clinical Outcome Ofsupporting
confidence: 94%
See 1 more Smart Citation
“…By 6 dpc, mice in G3 (high virus dose/vehicle, white symbols) showed about 20% weight loss and by 8 dpc there were no survivors because they have either succumbed to the infection or had to be humanely euthanized due to severe clinical signs (lethargy, ruffled fur, labored breathing, and/or ≥25% body weight loss, Fig 2D). These observations are consistent with previous reports 20,21,24,25 . G4 mice (high virus dose/GC-376) showed similar clinical signs but such progression was delayed by about 24 h (~15% weight loss by 6 dpc).…”
Section: Modest Effect Of Gc-376 Treatment On the Clinical Outcome Ofsupporting
confidence: 94%
“…Since then, several reports have emerged and our results are in agreement with the notion that the K18-hACE2 mouse model is a suitable small animal model to study SARS-CoV-2 pathogenesis 20,21,25 . Previous reports have also shown that K18-hACE2 mice are amenable for the study of vaccines against SARS-CoV-2 24 but, to our knowledge, assessment of this mouse model for the evaluation of potential antivirals against SARS-CoV-2 was lacking.…”
Section: Effects Of Gc-376 Treatment On Sars-cov-2-induced Pathology mentioning
confidence: 98%
“…2D). These observations are consistent with previous reports 16,17,20,21 . G4 mice (high virus dose/GC-376) showed similar clinical signs but such progression was delayed by about 24 h (~ 15% weight loss by 6 dpc).…”
Section: Effect Of Gc-376 Treatment On the Clinical Outcome In Mice Challenged With Sars-cov-2supporting
confidence: 94%
“…Sinovac Biotech and Sinopharm are at present conducting phase 3 trials on inactivated vaccines. [32][33][34]…”
Section: Inactivated Virus Vaccinesmentioning
confidence: 99%